Developing a biomaterial interface based on poly(lactic acid) via plasma-assisted covalent anchorage of d-glucosamine and its potential for tissue regeneration - Swilem, Ahmed E; Lehocký, Marian; Humpolíček, Petr; Kucekova, Zdenka; Junkar, Ita; Mozetič, Miran; Hamed, Ashraf A; Novák, Igor (Colloids and surfaces. B, Biointerfaces, 2016)
The aim of this study was to develop the potential tissue engineering applications of d-glucosamine (GlcN) immobilized onto the surface of a biodegradable matrix in order to induce a desired biological effect at biointerfaces. Thus, for sample preparation we used a novel multistep physicochemical approach. In the first step the poly(lactic acid) (PLA) films were exposed to a low pressure plasma in air atmosphere, followed by radical graft copolymerization with acrylic acid to yield a carboxyl-functionalized spacer layer on the PLA surface. The carboxyl groups were then coupled to GlcN molecules via the carbodiimide chemistry. The developed surfaces were characterized by X-ray Photoelectron Spectroscopy (XPS), Contact angle measurements and Atomic Force Microscopy (AFM). A preliminary study on the proliferation of fibroblasts on the developed surfaces was performed using the NIH/3T3 cell line.
Keywords: Regeneration; Photoelectron Spectroscopy; polyestery; Glucosamine; Cell Proliferation; Microscopy, Atomic Force; povrchové vlastnosti; fotoelektronová spektroskopie; biokompatibilní materiály; Tissue Engineering; mikroskopie atomárních sil; Biocompatible Materials; proliferace buněk; Surface Properties; Polyesters; glukosamin; regenerace; smáčivost; tkáňové inženýrství; Wettability